Finding low CHA2DS2-VASc scores unreliable? Why not give morphological and hemodynamic methods a try? - Sun, YiRen; Ling, Yunfei; Chen, Zijia; Wang, Zhengjie; Li, Tao; Tong, Qi; Qian, Yongjun (Frontiers in Cardiovascular Medicine, 2023)
Patients with atrial fibrillation (AF) suffer from high risk of thrombosis. Currently CHA2DS2-VASc score is the most widely used tool for the risk stratification of them, but with disappointing accuracy and limited predictive value, especially in those with low score. AF patients’ thrombus mostly grow in their left atrial appendages (LAA), which is directly related to the abnormal morphology of LAA or left atrium and the unusual hemodynamic state around LAA, which may sensitively evaluate the risk of thrombosis complications in AF patients, bring bases to clinical plans of medication and operation. So we investigated the research progress of hemodynamic and morphological studies about their predictive value of AF patients’ thrombosis risk, intending to discuss the prediction potential of morphological and hemodynamic indexes when compared with presently used CHA2DS2-VASc system, and how to build a more precise thromboembolic event prediction model for AF patients.